KONFLIK NORMA PADA PEMBIAYAAN PENEMPATAN PEKERJA MIGRAN INDONESIA - Octaviani, Putu Tantry; Siki Layang, I Wayan Bela (Kertha Semaya : Journal Ilmu Hukum, 2022)
Tujuan penelitian ini adalah untuk memberi pemahaman mengenai pengaturan pembiayaan penempatan pekerja migran di Indonesia dan untuk memahami akibat hukum terjadinya konflik norma terkait pembiayaan penempatan pekerja migran Indonesia. Metode yang dipergunakan pada artikel terkait konflik norma pada pembiayaan penempatan PMI ini mempergunakan penelitian hukum yuridis normatif, dengan pendekatan perundang-undangan dan pendekatan konseptual. Hasil penelitian menunjukkan yakni jika Pengaturan pembiayaan penempatan pekerja migran di Indonesia pada dasarnya sudah dilakukan pengaturan melalui “ UU No. 13.2003 tentang Ketenagakerjaan; UU No. 6/2012 tentang Pengesahan International Convention on The Protection of The Rights of All Migrant Worker and Member of Their Families (Konvensi internasional mengenai perlindungan hak-hak seluruh pekerja migran dan anggota keluarganya); UU No. 18/2017 tentang Pelindungan Pekerja Migran Indonesia; PP No. 59/2021 tentang Pelaksanaan Pelindungan Pekerja Migran Indonesia”. Selanjutnya akibat hukum terjadinya konflik norma terkait pembiayaan penempatan pekerja migran Indonesia maka akan dilakukan pemanfaatan oleh pihak-pihak yang tidak dapat dipertanggungjawabkan, pematokan harga tinggi (overcharging) saat proses ditempatkannya PMI, dan penipuan yang lebih menjurus pada tindak pidana perdagangan orang. The purpose of this study is to provide an understanding of the financing arrangements for the placement of migrant workers in Indonesia and to understand the legal consequences of conflicting norms regarding the financing of the placement of Indonesian migrant workers. The method used in this article related to the conflict of norms in the financing of PMI placements uses normative juridical legal research, with a statutory approach and a conceptual approach. The results of the study show that if the arrangement for financing the placement of migrant workers in Indonesia has basically been carried out through "Law no. 13.2003 concerning Manpower; UU no. 6/2012 concerning Ratification of the International Convention on The Protection of The Rights of All Migrant Workers and Members of Their Families (international convention on the protection of the rights of all migrant workers and members of their families); UU no. 18/2017 concerning the Protection of Indonesian Migrant Workers; PP No. 59/2021 concerning the Implementation of the Protection of Indonesian Migrant Workers”. Furthermore, the legal consequences of conflicts of norms related to the financing of the placement of Indonesian migrant workers will be exploited by parties who cannot be accounted for, high price fixing (overcharging) during the process of placing PMI, and fraud which is more likely to lead to criminal acts of trafficking in persons.